Pengaruh Personal Hygiene dan Penggunaan Alat Pelindung Diri dengan Keluan Gangguan Kulit pada Pemulung di Pembuangan Akhir Suwung - Ida Ayu Indira Meliana Putri Suteja; Luh Gede Evayanti; Made Sudarjana (Aesculapius Medical Journal, 2023)
Scavengers work and often interact closely with trash and many other highly contaminated things. Thus, they are very prone to get infected by skin disease. It was all due to the lack of personal hygiene’s implementation and the use of personal protective equipment (PPE) which increase the risk of catching skin disease. This research was done to find out the relation between personal hygiene and the use of personal protective equipment with the number of scavengers infected with skin disease at Suwung’s landfills (TPA). This research was using an analytic research type with a cross sectional research design which was done during December 2021 to January 2022. The sampling technique was using purposive sampling with 161 respondents. The data collection was using questionnaire. The data analysis was using SPSS type 25 and Chi-square. The final result from the bivariate analysis showed a relation between personal hygiene and the use of PPE with the number of scavengers infected with skin disease at Suwung’s landfills (TPA) (P<0,005). In conclusion, poor personal hygiene and the lack of Personal protective equipment’s usage during work can increase the risk of these scavengers to get infected by skin disease. Keywords: personal hygiene, personal protective equipment, scavengers, skin disease.